Banach-Mazur Distance Between Two Dimensional Banach Spaces
The purpose of the present paper is to investigate geometric properties of two-dimensional Banach spaces. We are also concerned with the Banach-Mazur distance between Banach spaces. For real or complex spaces d(l^2_1,l^2_p)= 2^1-1p , if 1≤ p≤ 2 and if 1≤ p≤ ∞ and l_p^2 is two-dimensional real space, then d(l^2_1,l^2_p)= 2^1p . 1991 Mathematics Subject Classification. 46B03, 46B03 , number=2, journal=Sarajevo Journal of Mathematics, author=Al-Mezel, S. A., year=2024, month=Jun., pages=205–210